Absence of Transverse Tubules Contributes to Non-Uniform Ca(2+) Wavefronts in Mouse and Human Embryonic Stem Cell–Derived Cardiomyocytes - Lieu, Deborah K. (Mary Ann Liebert, Inc. publishers, 2009)
Mouse (m) and human embryonic stem cell-derived cardiomyocytes (hESC-CMs) are known to exhibit immature Ca(2+) dynamics such as small whole-cell peak amplitude and slower kinetics relative to those of adult. In this study, we examined the maturity and efficiency of Ca(2+)-induced Ca(2+) release in m and hESC-CMs, the presence of transverse (t) tubules and its effects on the regional Ca(2+) dynamics. In m and hESC-CMs, fluorescent staining and atomic force microscopy (AFM) were used to detect the presence of t-tubules, caveolin-3, amphiphysin-2 and colocalization of dihydropyridine receptors (DHPRs) and ryanodine receptors (RyRs). To avoid ambiguities, regional electrically-stimulated Ca(2+) dynamics of single ESC-CMs, rather than spontaneously beating clusters, were measured using confocal microscopy. m and hESC-CMs showed absence of dyads, with neither t-tubules nor colocalization of DHPRs and RyRs. Caveolin-3 and amphiphysin-2, crucial for the biogenesis of t-tubules with robust expression in adult CMs, were also absent. Single m and hESC-CMs displayed non-uniform Ca(2+) dynamics across the cell that is typical of CMs deficient of t-tubules. Local Ca(2+) transients exhibited greater peak amplitude at the peripheral than at the central region for m (3.50 ± 0.42 vs. 3.05 ± 0.38) and hESC-CMs (2.96 ± 0.25 vs. 2.72 ± 0.25). Kinetically, both the rates of rise to peak amplitude and transient decay were faster for the peripheral relative to the central region. Immature m and hESC-CMs display unsynchronized Ca(2+) transients due to the absence of t-tubules and gene products crucial for their biogenesis. Our results provide insights for driving the maturation of ESC-CMs.